Quality Assurance of Higher Education in Alberta and Norway: Lessons for Kenya - James Alan Oloo (Arizona State University, 2010)
Debate about academic quality assurance has often tended to bring into the fore extensive dispute about the meaning of the phrase. However, many observers appreciate the importance of quality assurance and enhancement of degree programming. In this paper, I review issues in quality assurance of higher education in the Province of Alberta, Canada, Norway, and Kenya and outline possible lessons for Kenya and other developing countries.